Cleaner strategies on the effective elimination of toxic chromium from wastewater using coupled electrochemical/biological systems. Issue 4 (13th January 2020) - Pavithra, Kirubanandam Grace; Jaikumar, Vasudevan; Kumar, Ponnusamy Senthil; Sundarrajan, Panneerselvam
Abstract: Hexavalent chromium is a toxic pollutant and carcinogen, which affects the organs internally as well as externally in our body. In this research, a combination of three‐dimensional (3D)‐electrochemical treatment followed by biological treatment was done for chromium removal in simulated wastewater. Surface‐modified Strychnos potatorum (SMSp) seeds and surface‐modified tamarind pod (SMTp) shell were used as particle electrodes, and the experiments were conducted for different pH, voltage, and particle electrode followed by biological treatment. In biological treatment, Enterobacter cloacae strain was isolated from a common effluent treatment plant (CETP) and it was utilized. The molecular characterization of E. cloacae (live biomass) was done using 16s rRNA sequencing. In 3D‐electrochemical treatment with SMSp, efficiency was found to be the best when compared with SMTp under optimum condition (6 V, 3 pH, 15 g of SMSp) at a working period of 60 min, and the removal of hexavalent chromium from aqueous solution using SMSp was successfully applied to semi‐empirical kinetic model, which is based on Fermi's equation. This semi‐empirical kinetic model effectively depicts the hexavalent chromium concentration evolution in 3D‐electrochemical treatment. The combined treatment reduced the amount of chemical oxygen demand as well as the hexavalent chromium‐ion concentration in aqueous solution.